Shattering the Stereotypes: Muslim Women Speak Out by Fawzia Afzal-Khan, ed. (Northampton, MA: Olive Branch Press, 2005. 338 pages.) (American Journal of Islam and Society, 2005)
Ever since the West’s initial contact with the East, Muslim women haveoccupied center stage as highly politicized subjects who the West hasclaimed to liberate from the oppressive East and who the East has claimedto protect from the hedonistic West. Despite their central role as pawns inthis political struggle, women have been strikingly silent subjects. Thisbook belongs to an emerging collection of books that seek to give voice tothese silent subjects. Nawal El Saadawi, in her emotionally charged“Foreword,” captures the book’s tone quite well in her expression that “thepersonal is political” (p. x). Through personal stories, this anthology seeksto dissociate Islam from both terrorism and the oppression of women.Fawzia Afzal-Khan’s anecdotal introduction reveals that her goal istwofold: first, to connect various strands of conversation between MuslimAmerican women from different backgrounds since 9/11, and, second, toenlighten both Muslim and non-Muslim readers of the varied realities of the“Muslim Woman.”This anthology is divided into six sections. Section 1, “Non-Fiction,”contains several personal accounts of Muslim American women’s encounterswith 9/11. In her piece “Unholy Alliances,” Afzal-Khan vents her frustrationon several targets, including Israel, American foreign policy, SalmanRushdie, women who choose to wear the hijab, as well as the MontclairUniversity Muslim Students’ Association and the Global Studies Institute.Nadia Ali Maiwandi, Zohra Saed, and Wajma Ahmady reflect on theresponses they encountered and experienced amidst the Afghan-Americancommunity in the aftermath of 9/11. Eisa Nefertari Ulen’s genuinely tolerantarticle encourages Muslim and non-Muslim women to work together.Writing from her perspective as an African-American convert, she identifiesissues of gender and religion as mere smokescreens used by the “oppressor”to separate women (p. 50). Humera Afridi’s witty and refreshing work functionsas a social commentary on the climate of New York City after the 9/11attacks. One of the most edifying pieces is Rabab Abdulhadi’s “Where isHome?” This piece, written as a series of journal entries, captures the strugglesof identity faced by an exiled Palestinian woman as she tries to make ahome in New York City in the aftermath of 9/11 ...